Controversial Screening for Thyroid Dysfunction in Preconception and Pregnancy: An Evidence-Based Review - Joana Lima Ferreira; Mafalda Gomes; Rosa Maria Príncipe (Tehran University of Medical Sciences, 2021)
Objective: To evaluate the recommendations on the most adequate screening method (universal or selective) for thyroid dysfunction. Although thyroid dysfunction is a common disorder in fertile women and untreated cases may have negative maternal, fetal and neonatal outcomes, its screening in preconception and early pregnancy is controversial. Materials and methods: An evidence-based review was conducted to identify publications since 2017 of American Thyroid Association (ATA) guidelines, according to the following Population, Intervention, Comparison, Outcomes and Study (PICOS): women in preconception or pregnancy without thyroid disease who underwent universal or selective screening for thyroid dysfunction. Study selection obeyed the PRISMA criteria. Results: We included 15 of 325 publications. The 2017 ATA guidelines recommend selective screening in both preconception and pregnancy. The only two reviews on preconception recommended universal screening. For pregnancy, nine articles suggested universal screening, while a prospective study advocated selective screening. The main benefits advocated for universal screening were easy and low-cost tests; absence of missed diagnosis; safe and inexpensive treatment and its potential in preventing negative outcomes. Iodine deficiency is a decisive indication, but it was not evaluated in all clinical studies. Screening harms and knowledge gaps were the main arguments against universal screening. There are very few cost-effectiveness studies. Conclusion: We recommend universal screening for thyroid dysfunction in early pregnancy, which is a distinct point of view from 2017 ATA guidelines (weak recommendation, low-quality evidence). It is not possible to make a formal recommendation for preconception (insufficient evidence). We strongly suggest an individualized analysis by each country.